The effect of feed ingredients on feed manufacturing and growth performance of pigs - Groesbeck, Crystal Noel (Kansas State University, 2007)
Two experiments evaluated effects of glycerol on pellet mill production and pig performance. In Exp. 1, increasing glycerol increased (quadratic; P < 0.01) pellet durability index through 9% added glycerol. Adding glycerol decreased (linear; P > 0.01) production energy (kWh/t). In Exp. 2, pigs were fed one of seven diets with no added soy oil or glycerol (control); the control diet with 3 or 6% added soy oil, 3 or 6% added glycerol, and 6 or 12% additions of a 50:50 soy oil/glycerol blend in a 26-d growth assay. Adding glycerol improved (P < 0.01) pellet durability compared to soy oil and the soy oil/glycerol blend treatments. Pigs fed glycerol had increased (linear, P < 0.03) ADG. Adding soy oil, glycerol, or the soy oil/glycerol blend resulted in similar final BW. Two experiments evaluated the effects of glycerol as a replacement for lactose on pellet mill production and nursery pig performance. In Exp. 1, pigs were fed one of ten treatments that included 0, 3.6, or 7.2% lactose or 0, 3.6, or 7.2 % glycerol and fed in either meal or pelleted form. Pellet durability index increased (linear; P < 0.01) with added lactose and glycerol. Glycerol decreased (linear; P < 0.01) production energy (kWh/t). There was a tendency (P < 0.06) for an inclusion level × diet form (meal or pellet) interaction observed for ADG. Pigs fed the pelleted diets containing the 7.2% glycerol inclusion had decreased ADG compared to all other treatments. In Exp. 2, pigs were fed one of fourteen diets that included 0, 3.6, 7.2, or 10.8% lactose or 0, 3.6, 7.2, or 10.8 % glycerol and fed in either meal or pelleted form. There was no effect (P < 0.27) of diet form, inclusion level, or source on ADG or ADFI. Eight experiments evaluated the effect of ingredients on the flow ability of ground corn. Flow ability of feed improved with added glycerol, especially when added to meal diets containing hammer mill ground corn. Specialty protein ingredients in powder form reduce flow ability, while fine lactose sources improved flow ability. Granulated ingredients improved flow ability.
Keywords: Angle of repose; glycerol; pig; pellet; Agriculture, Animal Culture and Nutrition (0475)